Associations between Health Effects and Particulate Matter and Black Carbon in Subjects with Respiratory Disease - Jansen, Karen L.; Larson, Timothy V.; Koenig, Jane Q.; Mar, Therese F.; Fields, Carrie; Stewart, Jim; Lippmann, Morton (Environmental health perspectives, 2005)
We measured fractional exhaled nitric oxide ( FENO), spirometry, blood pressure, oxygen saturation of the blood ( SaO2), and pulse rate in 16 older subjects with asthma or chronic obstructive pulmonary disease (COPD) in Seattle, Washington. Data were collected daily for 12 days. We simultaneously collected PM10and PM2.5(particulate matter ≤ 10 μm or ≤ 2.5 μm, respectively) filter samples at a central outdoor site, as well as outside and inside the subjects' homes. Personal PM10filter samples were also collected. All filters were analyzed for mass and light absorbance. We analyzed within-subject associations between health outcomes and air pollution metrics using a linear mixed-effects model with random intercept, controlling for age, ambient relative humidity, and ambient temperature. For the 7 subjects with asthma, a 10 μ g/ m3increase in 24-hr average outdoor PM10and PM2.5was associated with a 5.9 [95% confidence interval (CI), 2.9-8.9] and 4.2 ppb (95% CI, 1.3-7.1) increase in FENO, respectively. A 1 μ g/ m3increase in outdoor, indoor, and personal black carbon (BC) was associated with increases in FENOof 2.3 ppb (95% CI, 1.1-3.6), 4.0 ppb (95% CI, 2.0-5.9), and 1.2 ppb (95% CI, 0.2-2.2), respectively. No significant association was found between PM or BC measures and changes in spirometry, blood pressure, pulse rate, or SaO2in these subjects. Results from this study indicate that FENOmay be a more sensitive marker of PM exposure than traditional health outcomes and that particle-associated BC is useful for examining associations between primary combustion constituents of PM and health outcomes.